2021
DOI: 10.1186/s12864-021-07967-7
|View full text |Cite
|
Sign up to set email alerts
|

A complete mitochondrial genome for fragrant Chinese rosewood (Dalbergia odorifera, Fabaceae) with comparative analyses of genome structure and intergenomic sequence transfers

Abstract: Background Dalbergia odorifera is an economically and culturally important species in the Fabaceae because of the high-quality lumber and traditional Chinese medicines made from this plant, however, overexploitation has increased the scarcity of D. odorifera. Given the rarity and the multiple uses of this species, it is important to expand the genomic resources for utilizing in applications such as tracking illegal logging, determining effective population size of wild stands, delineating pedig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…The complete cp genome sequences have been extensively used to reconstruct plant phylogeny [ 3 , 21 ]. In contrast, mt genome sequences appear to have been relatively scarce in this respect [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete cp genome sequences have been extensively used to reconstruct plant phylogeny [ 3 , 21 ]. In contrast, mt genome sequences appear to have been relatively scarce in this respect [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrion plays an important role in metabolic processes. It provides energy for eukaryotes and is the site of ATP synthesis [ 3 ]. The mitochondrial (mt) genomes of plants are large and complex, with a length of 200–2000 kbp and a variable structure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant mitogenomes have evolved from with dramatic and rapid structural changes, thus many unique features can be found compared with conserved plant plastomes and compact animal mitogenomes. These features include huge genome size variations, active multipartite arrangements, low gene density, abundant post-transcribed RNA editing, gene sequence transfer or loss, and foreign sequence capture ( Hong et al., 2021 ; Wu et al., 2022 ). Although plant mitogenomes are conventionally reported as circular structures, much like the circular chromosomes found in animal mitochondria and bacteria, many studies have shown that the simple circular model of genome structure that applies to most animal species is inadequate when trying to understand plant mitochondria that can have multiple circular replicons, branched, linear, or mixed forms of genomic structure, i.e., Silene noctiflora has a mitogenome that is arranged into numerous circular chromosomes, that is, one ring cannot rule them all ( Sloan, 2013 ; Wu et al., 2015 ) based on mapping to a circular reference.…”
Section: Discussionmentioning
confidence: 99%
“…angulari, Phaseolus vulgaris L., Cicer arietinum, Arachis hypogaea, Astragalus membranaceus var. mongholicus, Hedysarum polybotrys [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%